Cellular phenotypic transitions in diabetic nephropathy: an update - Cao, Yi-Ling; Lin, Ji-Hong; Hammes, Hans-Peter; Zhang, Chun (Frontiers in pharmacology, 2022)
Diabetic nephropathy (DN) is a major cause of morbidity and mortality in diabetes and is the most common cause of end stage renal disease (ESRD). Renal fibrosis is the final pathological change in DN. It is widely believed that cellular phenotypic switching is the cause of renal fibrosis in diabetic nephropathy. Several types of kidney cells undergo activation and differentiation and become reprogrammed to express markers of mesenchymal cells or podocyte-like cells. However, the development of targeted therapy for DN has not yet been identified. Here, we discussed the pathophysiologic changes of DN and delineated the possible origins that contribute to myofibroblasts and podocytes through phenotypic transitions. We also highlight the molecular signaling pathways involved in the phenotypic transition, which would provide valuable information for the activation of phenotypic switching and designing effective therapies for DN.
Gesehen am 10.07.2023